PENGARUH MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA SISWA KELAS I SDN MOROKREMBANGAN I SURABAYA - Agung Prasetio, Ahmad; Widiana Rahayu, Dewi; Ghufron, Syamsul; Umar Susanto, Rudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine students' reading ability before and after the implementation of the Big Book media and to analyze the effect of using Big Book media on the beginning reading ability of first-grade students at SDN Morokrembangan I Surabaya. This study employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The research subjects consisted of 20 first-grade students at SDN Morokrembangan I Surabaya. Data were collected through reading ability tests administered as a pretest and posttest, as well as documentation. The data were analyzed using descriptive statistics and inferential statistics through a t-test. The results showed that the students' reading ability before the implementation of the Big Book media had a mean score of 56.50, which was categorized as low, with a learning mastery level of 29.62%. After the implementation of the Big Book media, the mean score increased to 76.75, which was categorized as high, with a learning mastery level reaching 87.55%. The t-test analysis revealed that the calculated t-value (14.36) was higher than the t-table value (1.70) at the 5% significance level (14.36 > 1.70). Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. It can be concluded that the use of Big Book media has a significant effect on improving the beginning reading ability of first-grade students at SDN Morokrembangan I Surabaya. The Big Book media effectively increased students' learning interest and facilitated their ability to recognize letters, syllables, words, and simple sentences. Therefore, it is considered an appropriate instructional medium for teaching beginning reading in elementary schools.